2017
DOI: 10.1038/s41598-017-09032-4
|View full text |Cite
|
Sign up to set email alerts
|

Metagenomic analysis reveals a green sulfur bacterium as a potential coral symbiont

Abstract: Coral reefs are ecologically significant habitats. Coral-algal symbiosis confers ecological success on coral reefs and coral-microbial symbiosis is also vital to coral reefs. However, current understanding of coral-microbial symbiosis on a genomic scale is largely unknown. Here we report a potential microbial symbiont in corals revealed by metagenomics-based genomic study. Microbial cells in coral were enriched for metagenomic analysis and a high-quality draft genome of “Candidatus Prosthecochloris korallensis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 59 publications
(70 reference statements)
1
31
0
Order By: Relevance
“…Vibrionales) (Olson et al, 2009;Lema et al, 2012;Olson and Lesser, 2013;Lema et al, 2014b;Santos et al, 2014;Yang et al, 2015;Lesser et al, 2018). Only one study identified Chlorobia to clearly dominate (>80%) the diazotrophic community in a tropical coral (Yang et al, 2015), which, besides N 2 fixation, potentially reveals additional ecological functions for the coral host such as anoxygenic photosynthesis, C fixation and sulfur oxidation (Yang et al, 2016;Cai et al, 2017). The high relative abundance of potentially autotrophic as compared with heterotrophic diazotrophs in O. patagonica suggests that these bacteria may provide, besides DDN, also fixed C to the coral host.…”
Section: Discussionmentioning
confidence: 99%
“…Vibrionales) (Olson et al, 2009;Lema et al, 2012;Olson and Lesser, 2013;Lema et al, 2014b;Santos et al, 2014;Yang et al, 2015;Lesser et al, 2018). Only one study identified Chlorobia to clearly dominate (>80%) the diazotrophic community in a tropical coral (Yang et al, 2015), which, besides N 2 fixation, potentially reveals additional ecological functions for the coral host such as anoxygenic photosynthesis, C fixation and sulfur oxidation (Yang et al, 2016;Cai et al, 2017). The high relative abundance of potentially autotrophic as compared with heterotrophic diazotrophs in O. patagonica suggests that these bacteria may provide, besides DDN, also fixed C to the coral host.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence of sulfur oxidation in microbiomes of other sponges 77,78 corals 79 , and other invertebrates 80 suggests this is a common energy source for symbiotic microbes, although it could be regulated by diurnal fluctuations in oxygen concentration in M. cavernosa. Transcripts for a thiosulfate transporter (cysP) were recovered from M. cavernosa (Fig.…”
Section: Functional Overview Of the Sponge And Coral Microbiome Profmentioning
confidence: 99%
“…For plausibility, an analogous event has occurred more recently. Coral, a eukaryote, has a ''green sulfur bacterium as a potential coral symbiont'' (Cai et al, 2017). Modern eukaryotes that lack mitochondria have mitochondrial genes in their nuclei; their ancestors, thus, jettisoned their mitochondria in the past (e.g., Martin and Müller, 1998).…”
Section: Geological and Geochemical Constraints On Life 1207mentioning
confidence: 99%